Effect of Soil Management Practices on Soil Physico-Chemical Properties: A Case of Wera Sub-Watershed, Southern Ethiopia. (16th September 2022) - Sinore, Tamrat; Chernet, Mulatu; Detamo, Kibemo; Yohannes, Mekiso
Abstract : Soil degradation is a global challenge for agricultural productivity. To tackle this, the Ethiopian government and different NGOs launched soil management technologies in different parts of Ethiopia, including the Wera sub-watershed in Anlemo district, southern Ethiopia. This study was carried out to investigate the effect of soil management practices on soil properties at various landscape positions in the Wera sub-watershed. To achieve the intended objective, the 27 composite soil samples were collected from soil bund with desho grass, fanya-juu with desho grass and no management practices (control) with three replications at three landscape positions from 0 to 30 cm depth whereas, 27 undisturbed soil samples were collected for bulk density analysis. The collected soil samples were analyzed for soil texture, soil reaction, cation exchange capacity, organic carbon, total nitrogen, and available phosphorus. The result showed that soil bund with desho grass and fanya-juu with desho grass were significantly influenced selected soil physico-chemical properties when compared with no management measures. In addition, landscape position has significantly (p ≤ 0.05 ) influenced the selected physico-chemical properties of soil. Hereafter, soil bund with desho grass and fanya-juu with desho grass practices were found to be effective in changing landscape positions and advancing soil productiveness. Therefore, implementing soil bund with desho grass and fanya-juu with desho grass by considering landscape position is vital for increasing soil productivity via minimizing soil loss.